A Study on Bending Stiffness Characterization of Biohybrid Microrobots using External Magnetic Actuation - Dias, João Miguel Sameiro (2021)
Dissertação de Mestrado Integrado em Engenharia Biomédica apresentada à Faculdade de Ciências e Tecnologia